2008
DOI: 10.1002/hyp.6904
|View full text |Cite
|
Sign up to set email alerts
|

Fire effects on rangeland hydrology and erosion in a steep sagebrush‐dominated landscape

Abstract: Abstract:Post-fire runoff and erosion from wildlands has been well researched, but few studies have researched the degree of control exerted by fire on rangeland hydrology and erosion processes. Furthermore, the spatial continuity and temporal persistence of wildfire impacts on rangeland hydrology and erosion are not well understood. Small-plot rainfall and concentrated flow simulations were applied to unburned and severely burned hillslopes to determine the spatial continuity and persistence of fire-induced i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
222
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 114 publications
(231 citation statements)
references
References 37 publications
8
222
0
1
Order By: Relevance
“…For this reason, the unit-area peak discharge is considered to be the most sensitive parameter for the description of the modified watershed response after a wildfire (e.g., Rowe et al 1954). More specifically, experimental analyses conducted both in Europe and in the United States indicate that the annual peak discharge in postfire conditions can increase by a factor generally ranging from 1.2 to 6.5 (Hoyt & Troxell 1934, Anderson 1976, Hessling 1999, Loáiciga et al 2001, Conedera et al 2003, Rulli & Rosso 2007, Pierson et al 2008, Seibert et al 2010 and can even exceed 100 in some cases (Campbell et al 1977, Bolin & Ward 1987, Neary et al 2003. However, there have been some case studies (Britton 1991, Aronica et al 2002, Bart & Hope 2010 in which little or no increase in postfire discharges were observed.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, the unit-area peak discharge is considered to be the most sensitive parameter for the description of the modified watershed response after a wildfire (e.g., Rowe et al 1954). More specifically, experimental analyses conducted both in Europe and in the United States indicate that the annual peak discharge in postfire conditions can increase by a factor generally ranging from 1.2 to 6.5 (Hoyt & Troxell 1934, Anderson 1976, Hessling 1999, Loáiciga et al 2001, Conedera et al 2003, Rulli & Rosso 2007, Pierson et al 2008, Seibert et al 2010 and can even exceed 100 in some cases (Campbell et al 1977, Bolin & Ward 1987, Neary et al 2003. However, there have been some case studies (Britton 1991, Aronica et al 2002, Bart & Hope 2010 in which little or no increase in postfire discharges were observed.…”
Section: Introductionmentioning
confidence: 99%
“…One study found that interrill sediment erosion was doubled in a burned watershed compared to a neighboring unburned watershed, along with increases in runoff velocity due to increased bare ground coverage (Pierson et al, 2008(Pierson et al, , 2013. The relative extent of interrill compared with rill erosion depends upon local landscape and precipitation conditions, where higher precipitation intensity and steeper slopes can drive increased rill formation (Moody et al, 2013).…”
Section: Post-fire Erosionmentioning
confidence: 99%
“…The loss or reduction of vegetation cover due to fires creates the opportunity for raindrops to reach the soil surface at high velocity, without being slowed down by aboveground vegetation and overlying litter layers. Hence, the same amount or intensity of rainfall can mobilize more PyC, and bulk C, from soil post-fire than it would under unburned conditions if there is loss of vegetation or litter layers (Inbar et al, 1998;Beyers et al, 2005;Cerdà and Doerr, 2005;Pierson et al, 2008Pierson et al, , 2009Pierson et al, , 2013. Generally, low intensity precipitation events drive preferential transport of light carbonaceous material (higher enrichment ratios, higher concentration of C) (Schiettecatte et al, 2008;Wang et al, 2010).…”
Section: Climate and Hydrologymentioning
confidence: 99%
See 1 more Smart Citation
“…At these sites, rainfall exceeded the initial infiltration and storage capacity, thus initiating runoff resulting in a high occurrence of rill erosion (Pierson et al, 2008a).…”
Section: Hydrologic Factorsmentioning
confidence: 99%